Inclusive Education: Challenges and Solutions for Language Teachers - Chakanova Aizhan; Myrzakhanova D. (Foundations and Trends in Modern Learning, 2025)
This study explores the challenges faced by language teachers in implementing inclusive education in Kazakhstan and identifies practical solutions supported by both literature and teacher-reported data. A quantitative descriptive survey (N = 50) was conducted among English teachers from primary and secondary schools. Findings indicate strong teacher support for inclusive education, but significant challenges remain, including large class sizes, insufficient training, behavioural difficulties, and limited adapted materials. Three tables summarise teachers’ attitudes, challenges, and preferred solutions. The results highlight the importance of systemic teacher training, professional development, collaboration with specialists, and improved resource availability. The study provides recommendations for strengthening inclusive practices in Kazakhstani language classrooms